Model for intracellular folding of the human immunodeficiency virus type 1 gp120. - Fennie, C (1989)
The intracellular folding of the human immunodeficiency virus type 1 gp120 has been assessed by analyzing the ability of the glycoprotein to bind to the viral receptor CD4. Pulse-chase experiments revealed that the glycoprotein was initially produced in a conformation that was unable to bind to CD4 and that the protein attained the appropriate tertiary structure for binding with a half-life of approximately 30 min. The protein appears to fold within the rough endoplasmic reticulum, since blocking of transport to the Golgi apparatus by the oxidative phosphorylation inhibitor carbonyl cyanide m-chlorophenylhydrazone did not appear to perturb the folding kinetics of the molecule. The relatively lengthy folding time was not due to modification of the large number of N-linked glycosylation sites on gp120, since inhibition of the first steps in oligosaccharide modification by the inhibitors deoxynojirimycin or deoxymannojirimycin did not impair the CD4-binding activity of the glycoprotein. However, production of the glycoprotein in the presence of tunicamycin and removal of the N-linked sugars by endoglycosidase H treatment both resulted in deglycosylated proteins that were unable to bind to CD4, suggesting in agreement with previous results, that glycosylation contributes to the ability of gp120 to bind to CD4. Interestingly, incomplete endoglycosidase H treatment revealed that a partially glycosylated glycoprotein could bind to the receptor, implying that a subset of glycosylation sites, perhaps some of those conserved in different isolates of human immunodeficiency virus type 1, might be important for binding of the viral glycoprotein to the CD4 receptor.